THEO VAN LEEWEN'S CRITICAL DISCOURSE ANALYSIS OF REVIEW OF CHILD ACUTE RIDNEY FAILURE ON NEWS PORTAL JAWAPOS, MERDEKA.COM AND TEMPO.CO: ANALISIS WACANA KRITIS THEO VAN LEEWEN TENTANG TINJAUAN KEGAGALAN RIDNEY AKUT ANAK DI PORTAL BERITA JAWAPOS, MERDEKA.COM DAN TEMPO.CO - Komalasari, Ai; Hamdani, Agus (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This study aims to (1) describe and analyze the exclusion strategy on the news portal JawaPos, Merdeka.com, and Tempo.co in reporting cases of acute kidney failure in children, and (2) describe and analyze the inclusion strategy on the news portal JawaPos, Merdeka. com, and Tempo.co in reporting cases of acute kidney failure in children. The subject of this research is the news portal JawaPos, Merdeka.com, Tempo.co. The object of this research is the strategy of exclusion and inclusion in reporting cases of kidney failure caused by syrup drugs. The collection of news is based on purposive sampling technique, not all news is analyzed. The news closest to the research is selected. The results showed that (1) the exclusion strategy was widely used by the JawaPos portal (2) the inclusion strategy was widely used by the Tempo.co news portal in spreading the news. The conclusion of the research is that JawaPos uses more exclusion strategies (Passion) (100%) with the aim of hiding the perpetrators so that they do not appear in the news. On the other hand, Tempo.co tends to use an inclusion strategy (indifferentiation-differentiation) (49.8%) which is a strategy that provides additional information to corner certain subjects in the news rather than other strategies. Based on these conclusions, there are several suggestions that can be submitted, namely: (1) readers to be more critical and careful in sorting information, (2) media owners are expected to make news more balanced, (3) further research can be carried out by researchers outside the field. language, such as communication, and social.